Use of hydropower plants and its main problems - Akmalov Jamshidbek Xakimjon o‘g‘li; Ismoilov Hasanboy Abduvali o‘g‘li (Zien Journals, 2022)
The use of hydro resources in the article. A number of shortcomings have been addressed and the process has been analyzed. In the process, recommendations have been made to increase energy efficiency.
Keywords: Use; hydroelectric; equipment; Hydrotubbins